Specifični elementi v funkcijski zgradbi Ljubljane - Pak, Mirko (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2004)
The functional structure of Ljubljana is predominated by supply activities which form its own new city network. Particular attention shall be paid to four big supply centres and the interdependence of their development with the commercial function within the city centre. This has also been confirmed on the basis of the results of a questionnaire, with the reasons for the development processes pointed out, which are in favour of the big trade centres in Šiška, Moste, Rakovnik and Vič.
Keywords: urbana geografija; mesta; omrežja naselij; funkcije; raba prostora; Ljubljana